(untitled) (Journal of the College of Basic Education, 2022)
The Current research aims to identify the effect of teaching physics by using KWHLAQ strategy in the achievement & convergent thinking of the third intermediate Grade Students, the researcher chose Al- Sadiq Al-Ameen intermediate school for boys belongs to the General Directorate of Education Rusafa-2, intentionally from a community of his research, for the first semester of the academic year( 2019-2020) ,and The sample consisted of ( 70) students in two classes chosen randomly from six classes to represent the experimental and control groups and by ( 35) Students in each group , The researcher prepared the requirements of the experiment included (identifying Scientific subject , the behavioral objectives ,preparation of teaching plans for the two experimental & control groups ), the two groups have been rewarded in the following variables , the chronological age in months , the degree of intelligence scale " otis- Linion", the degree of convergent thinking test, the experimental group has been taught by using the KWHLAQ strategy & the control group by using the normal way , the tools for research has been applied, the achievement test in physics consists of ( 20 ) objectival items of the kind of multiple choice &five essay items and its psychometric properties are extracted , According to the convergent thinking test , the researcher has adopted the test (Al- mallki,2013 ),which includes( 30) items ,and after verifying its validity and stability, after completion the teaching of the prescribed curriculum ,The Achievement test and the convergent thinking test has been applied for the two groups , statistical methods has been used (difficulty factor, coefficient of discrimination strength equation and T-test and Person Correlation Coefficient and Alpha Kronbach equation ,to analyze the results showed the superiority of the experimental group Students over the control group Students in both the achievement test and the convergent thinking test , According to this situation, the researcher put a number of recommendation and proposals.